2008
DOI: 10.1021/bp049601a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inactivation of HSV-2 during Storage in Frozen and Lyophilized Forms

Abstract: The structural integrity of herpes simplex virus 2 (HSV-2) during freezing, thawing, and lyophilization has been studied using scanning and transmission electron microscopy. Viral particles should be thawed quickly from -80 to 37 degrees C to avoid artifacts of thawing. To avoid freezing damage, the virus should be rapidly frozen (>20 K s(-1)) rather than slowly frozen as occurs on the shelf of a lyophilizer (<1 K s(-1)). Fast freezing and thawing allows six cycles of freeze thaw with no loss of viral titer TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…These studies almost exclusively identified significant differences in vector competence with lower titer blood meals, yet our results clearly demonstrate that freezing/thawing of Zika virus significantly impairs infectivity to mosquitoes at a range of doses. Although the mechanistic basis of this difference has not been adequately studied and plaque assays did not indicate a decline in Zika virus infectious particles on Vero cell culture after freeze/thaw, differences in competence may be attributed to structural perturbations of the virion that inhibit efficient particle binding in vivo ( 31 ). Future studies characterizing Zika virus structure and binding could help elucidate the unique sensitivity of this virus to the negative effects of freeze/thaw.…”
Section: Discussionmentioning
confidence: 99%
“…These studies almost exclusively identified significant differences in vector competence with lower titer blood meals, yet our results clearly demonstrate that freezing/thawing of Zika virus significantly impairs infectivity to mosquitoes at a range of doses. Although the mechanistic basis of this difference has not been adequately studied and plaque assays did not indicate a decline in Zika virus infectious particles on Vero cell culture after freeze/thaw, differences in competence may be attributed to structural perturbations of the virion that inhibit efficient particle binding in vivo ( 31 ). Future studies characterizing Zika virus structure and binding could help elucidate the unique sensitivity of this virus to the negative effects of freeze/thaw.…”
Section: Discussionmentioning
confidence: 99%
“…Data pertaining to changes in flavivirus morphology due to freezing are lacking. Nevertheless, a study using electron microscopy found that another enveloped virus, herpes simplex virus 2 (HSV-2) (family Herpesviridae), that had been frozen and slowly thawed (4 °C) exhibited more irregularly shaped particles with damaged binding proteins, compared to quickly thawed (37 °C) HSV-2 (Hansen et al, 2005). The same study indicated no significant change in HSV-2 titers due to freezing; however, more viable virus particles were recovered when liquid nitrogen versus slow freezing was utilized.…”
Section: Effects Of Virus Preparation On Vector Competencementioning
confidence: 99%
“…This is a very probable explanation here as well, as adenoviruses form aggregates very readily (Galdiero 1979;Walkiewicz et al 2009). Uncoating of herpesviruses and consequent loss of infectivity during lyophilization without high concentration of protectants, especially sugars, has already been described by Grose et al (1981), Hansen et al (2005) and Zhai et al (2004). In the present study, in the medium without additives, obvious uncoating with corresponding titre loss due to lyophilization was observed in herpesviruses (BoHV-1) and paramyxoviruses (BPIV-3).…”
Section: Discussionmentioning
confidence: 76%